2020
DOI: 10.1101/2020.08.25.20181404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perturbations in the mononuclear phagocyte landscape associated with COVID-19 disease severity

Abstract: Monocytes and dendritic cells are crucial mediators of innate and adaptive immune responses during viral infection, but misdirected responses by these cells might contribute to immunopathology. A comprehensive map of the mononuclear phagocyte (MNP) landscape during SARS-CoV-2 infection and concomitant COVID-19 disease is lacking. We performed 25-color flow cytometry-analysis focusing on MNP lineages in SARS-CoV-2 infected patients with moderate and severe COVID-19. While redistribution of monocytes towards int… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 55 publications
6
42
0
Order By: Relevance
“…One potential such mechanism could be the downregulation of CD3ζ chain, that results in impaired T cell proliferation. CD3ζ chain downregulation on T cells has previously been observed in relation to MDSCs in several conditions including sepsis, hepatitis C infection and gastric cancer 39,40,41 21 . Previous research has shown age and male gender are risk factors for severe COVID-19 42 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…One potential such mechanism could be the downregulation of CD3ζ chain, that results in impaired T cell proliferation. CD3ζ chain downregulation on T cells has previously been observed in relation to MDSCs in several conditions including sepsis, hepatitis C infection and gastric cancer 39,40,41 21 . Previous research has shown age and male gender are risk factors for severe COVID-19 42 .…”
Section: Discussionmentioning
confidence: 85%
“…Single-cell RNA sequencing, mass cytometry and flow cytometry on blood have suggested that expansion of suppressive myeloid cells is a hallmark of severe COVID-19 20, 21 . Furthermore, high frequency of PMN-MDSCs was recently reported to correlate with disease severity in COVID-19 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a strong response of this subset may be important for an effective adaptive response to be mounted. 53 , 54 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, 17 patients were followed up at 5months and 13 patients were followed up at 9-months since symptom onset ( Figure 1A). This COVID-19 patient cohort is part of the Karolinska KI/K COVID-19 Immune Atlas project [16][17][18][19][20][21] . More clinical information and other related data can be found at covid19cellatlas.com.…”
Section: Study Subjects and Samplingmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID- 19), emerged in late 2019 and has since led to a pandemic resulting in deaths of more than 2 million people within just one year 1,2 . COVID-19 is primarily a respiratory disease with severity ranging from asymptomatic or mild infection to severe symptoms requiring hospitalization with oxygen supplementation or mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%